Paradoksy antyinflacyjnej polityki pieniężno-kredytowej banku angielskiego w latach 1988-1993 - Knakiewicz, Zenobia; Mika, Błażej (Wydział Prawa i Administracji UAM, 1997)
The paper characterizes the money and credit policy of the Bank of England in 1988-1993. The research was referred to original numerical data. The Bank has realized its policy in conformity with principles of closed loop policy despite of the fact that the imposed assumptions of its money and credit policy were based on the k per cent rule. Monitoring the volume of money resources and the inflation rate during this period denies any simple relations between these two factors. Within the period examined the index of money resources increased systematically up to 151,2 per cent. The inflation rate has increased from 4,9 to 9,5 in 1988 - 1991 and then dropped quickly to the level of 1,6 in 1993. The aim of the paper was to explain such a paradox. It appeared that open market operations of the type outright which were applied effected in the same way as it is for production credit.
Paradoxes of anti-inflation money and credit policy of the Bank of England in 1988 - 1993